Italy and the European Union - Bindi, Federiga M. (Brookings-SSPA series on public administration., 2011)
"Presents a comprehensive study of Italy's role in the European Union and what that country needs to do as a 'medium-sized power' to increase its influence in the EU, chiefly by putting forward well-defined goals and consistent strategies through credible actors"--Provided by publisher